An optimal far field radiation pattern synthesis of mutually coupled antenna arrays. Issue 7 (27th April 2022) - Das, Avishek; Mandal, Durbadal; Kar, Rajib
Abstract: This article presents a precise approach for far‐field radiation pattern (FFRP) correction of mutually coupled discrete dipole element (DDE) array of monopole antennas and concentric circular antenna array (CCAA) of dipole elements by employing the parametric assimilation technique (PAT). The effect of mutual coupling is a crucial part of any practical antenna array design issue. Various techniques have been suggested to calculate, compensate and reduce the mutual coupling effect during the last few decades. This article shows an exact method for mutual coupling inclusive corrected radiation pattern synthesis using PAT. The parameters of mutual impedance are calculated and assimilated with the values of the desired radiation pattern. The employed technique is cost‐effective, less complex and easy to implement while achieving better performance for mutually coupled DDE array and CCAA synthesis. Grey wolf optimisation (GWO) is a state‐of‐the‐art stochastic algorithm applied here to find the optimal values of the current amplitude excitation weights and the inter‐element spacing between each element of the array in the DDE array and three‐rings structure CCAA for the desired, uncorrected and corrected FFRP synthesis. Some well‐established evolutionary optimisation techniques like particle swarm optimisation (PSO), differential evolution (DE) and social spider algorithm (SSA) are also employed in this article for the sake of comparison with the results achieved by using the GWO algorithm. Finally, the supremacy of GWO algorithm based design is demonstrated and validated by employing the 16‐elements DDE array of monopole antennas and the three‐ring CCAA of dipole elements.